Synovial fluid monocyte-to-lymphocyte ratio in knee osteoarthritis patients predicts patient response to conservative treatment: a retrospective cohort study - Jong Min Lee; Sumin Lim; Gunoo Kang; Jun Young Chung; Hee-Woong Yun; Yong Jun Jin; Do Young Park; Jae-Young Park (BMC Musculoskeletal Disorders, 2024)
Abstract Background Biomarkers that predict the treatment response in patients with knee osteoarthritis are scarce. This study aimed to investigate the potential role of synovial fluid cell counts and their ratios as biomarkers of primary knee osteoarthritis. Methods This retrospective study investigated 96 consecutive knee osteoarthritis patients with knee effusion who underwent joint fluid aspiration analysis and received concomitant intra-articular corticosteroid injections and blood tests. The monocyte-to-lymphocyte ratio (MLR) and neutrophil-to-lymphocyte ratio (NLR) were calculated. After 6 months of treatment, patients were divided into two groups: the responder group showing symptom resolution, defined by a visual analog scale (VAS) score of ≤ 3, without additional treatment, and the non-responder group showing residual symptoms, defined by a VAS score of > 3 and requiring further intervention, such as additional medication, repeated injections, or surgical treatment. Unpaired t-tests and univariate and multivariate logistic regression analyses were conducted between the two groups to predict treatment response after conservative treatment. The predictive value was calculated using the area under the receiver operating characteristic curve, and the optimal cutoff value was determined. Results Synovial fluid MLR was significantly higher in the non-responder group compared to the responder group (1.86 ± 1.64 vs. 1.11 ± 1.37, respectively; p = 0.02). After accounting for confounding variables, odds ratio of non-responder due to increased MLR were 1.63 (95% confidence interval: 1.11–2.39). The optimal MLR cutoff value for predicting patient response to conservative treatment was 0.941. Conclusions MLR may be a potential biomarker for predicting the response to conservative treatment in patients with primary knee osteoarthritis.